Intranasal BMP9 Ameliorates Alzheimer Disease-Like Pathology and Cognitive Deficits in APP/PS1 Transgenic Mice - Wang, Zigao; Xiong, Lu; Wan, Wenbin; Duan, Lijie; Bai, Xiaojing; Zu, Hengbing (Frontiers in Molecular Neuroscience, 2017)
Alzheimer’s disease (AD) is the most common type of dementia and has no effective therapies. Previous studies showed that bone morphogenetic protein 9 (BMP9), an important factor in the differentiation and phenotype maintenance of cholinergic neurons, ameliorated the cholinergic defects resulting from amyloid deposition. These findings suggest that BMP9 has potential as a therapeutic agent for AD. However, the effects of BMP9 on cognitive function in AD and its underlying mechanisms remain elusive. In the present study, BMP9 was delivered intranasally to 7-month-old APP/PS1 mice for 4 weeks. Our data showed that intranasal BMP9 administration significantly improved the spatial and associative learning and memory of APP/PS1 mice. We also found that intranasal BMP9 administration significantly reduced the amyloid β plaques overall, inhibited tau hyperphosphorylation, and suppressed neuroinflammation in the transgenic mouse brain. Furthermore, intranasal BMP9 administration significantly promoted the expression of low-density lipoprotein receptor-related protein 1, an important membrane receptor involved in the clearance of amyloid β via the blood-brain barrier, and elevated the phosphorylation levels of glycogen synthase kinase-3β (Ser9), which is considered the main kinase involved in tau hyperphosphorylation. Our results suggest that BMP9 may be a promising candidate for treating AD by targeting multiple key pathways in the disease pathogenesis.